2013
DOI: 10.1142/s2335680413500178
|View full text |Cite
|
Sign up to set email alerts
|

Momentum Trading in New York Stock Exchange (Nyse) Energy Stocks

Abstract: This paper investigates whether the momentum effect exists in the NYSE energy sector. Momentum is defined as the strategy that buys (sells) these stocks that are best (worst) performers, over a pre-specified past period of time (the 'look-back' period), by constructing equally weighted portfolios. Different momentum strategies are obtained by changing the number of stocks included in these portfolios, as well as the look-back period. Next, their performance is compared against two benchmarks: the equally weigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
(15 reference statements)
0
3
0
Order By: Relevance
“…A limited number of studies have investigated energy markets using different tools for predictions, such as those of [11][12][13][14]. Chen et al [11] found that combining information content of oil price ranges and graphical information of time series provides more accurate predictions of oil price movements than traditional models.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A limited number of studies have investigated energy markets using different tools for predictions, such as those of [11][12][13][14]. Chen et al [11] found that combining information content of oil price ranges and graphical information of time series provides more accurate predictions of oil price movements than traditional models.…”
Section: Introductionmentioning
confidence: 99%
“…Chen et al [11] found that combining information content of oil price ranges and graphical information of time series provides more accurate predictions of oil price movements than traditional models. Based on 168 energy stocks included in the NYSE Energy Index, Thomakos and Papailias [14] observed a strong presence of the momentum effect in the energy sector of which risk-reward characteristics can be exploited through various momentum trading strategies. Lin et al [13] tested the predictive ability of technical trading rules proposed by Sullivan et al [15] based on daily returns for thirteen energy market indices.…”
Section: Introductionmentioning
confidence: 99%
“…While it is not possible to review the related literature in this paper, a number of representative references can provide a clear idea about the importance of energy sector investing. For example, see Papailias and Thomakos [7,8] who have employed an improved moving average methodology in energy related ETFs resulting in higher profits and decreased risk and investigate whether the momentum effect exist in the NYSE energy sector portfolio. They conclude that the momentum effect is strongly present in the energy sector, and leads to highly profitable portfolios, improving the risk-reward measures and easily outperforming typical performance benchmarks.…”
Section: Introductionmentioning
confidence: 99%